Copper nanoparticles selectively encapsulated in an ultrathin carbon cage loaded on SrTiO3 as stable photocatalysts for visible-light H2 evolution via water splitting. Issue 86 (2nd October 2019) - Tong, Lihang; Ren, Liteng; Fu, Ao; Wang, Defa; Liu, Lequan; Ye, Jinhua
Abstract : One-nanometre-thick carbon cage encapsulated copper nanoparticles synthesized through chemical vapour deposition showed remarkable stability in photocatalysis and thermocatalysis. Abstract : One-nanometre-thick carbon cage encapsulated copper nanopaticles on SrTiO3 (STO) synthesized through a facile chemical vapour deposition method showed remarkable stability and performance for both photocatalytic hydrogen evolution and thermocatalytic reduction of 4-nitrophenol. X-ray photoelectron spectroscopy and Raman results demonstrate that the graphene cage effectively protected Cu nanoparticles from being oxidized.